WBC and RBC Indicators among People with Hepatitis and Kidney Failure - Aljaff, Nora S. A.; Hameed, Shaymaa Jaber; Ibrahim, Ohood Abdullah (PT. Riset Press International, 2025)
The global pandemic of HBV and HCV infections produces liver insufficiency. This study examines blood markers in renal failure patients with and without viral hepatitis. The study included 90 blood samples from chronic renal failure patients (67 males and 23 females) undergoing hemodialysis (HD) in the unit. (HCV) and (HBV) were detected in patients' serum by ELISA, while WBC, RBC, lymphocyte, and neutrophil counts were measured using an automated hematology analyzer. This study assessed 90 CRF patients (67 men, 23 women). 22 men and 14 women (40%) had HBV and HCV; 60% (45 men and 9 women) did not. The HCV patient count was 20, and the HBV was 16. The average CRF patient had normal WBC levels (5.29.109/L). RBC counts were 3.25 x 1012/L in 64.44% of 58/90 patients, 26 with hepatitis virus, below the typical range of 3.5–5.5. The mean neutrophil count was 70.13 % higher than 50–70, and 59/90 (65.55%). 22 patients had hepatitis, with the highest value being 82. Within the normal 20-40 range, the lymphocyte % mean was 20.99. No significant difference (p>0.05).